COMMUNITY-BASED HUMAN RESOURCE COMPETENCY DEVELOPMENT THROUGH PERFUME PRODUCTION TRAINING TO INCREASE THE ECONOMIC VALUE OF LOCAL PRODUCTS - Rangga Putra Surya Adi Pradana; Mayvika Diniah Fani; Dwi Utami (Jurnal Pengabdian Bangsa, 2026)
This article examines the philosophical reconstruction of Christian Religious Education (CRE) as an instrument for building tolerance awareness within the multicultural society of Makassar City. Utilizing a qualitative research method based on library research and a hermeneutical-philosophical approach, this article analyzes the ontological, epistemological, and axiological foundations of CRE in the context of cultural, ethnic, and religious diversity in Makassar. Reconstruction is carried out on the paradigm, curriculum, methodology, and value orientation of CRE by integrating the thought of educational philosophers, multicultural theologians, and religious tolerance scholars. The findings indicate that philosophically reconstructed CRE can transcend doctrinal-exclusive approaches and transform into a dialogical pedagogy that situates the encounter with the "Other" as a formative moment of faith. The multicultural-tolerant CRE model formulated encompasses four dimensions: the theological-biblical dimension, the philosophical-hermeneutical dimension, the pedagogical-praxis dimension, and the socio-cultural dimension. These findings make a significant contribution to the development of contextual, inclusive, and relevant CRE for building a tolerant civil society in Makassar City.